2020
DOI: 10.1108/jamr-04-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the barriers to implementation of mass customization in Indian SMEs using integrated ISM-MICMAC and SEM

Abstract: PurposeThe purpose of this research is to identify the crucial barriers to the implementation of mass customization (MC) in Indian SMEs and to investigate the interactions among them so that important managerial implications could be formulated to facilitate the implementation of MC in SMEs.Design/methodology/approachThe contextual relationships and hierarchies of the barriers are established through the interpretive structural modelling (ISM) approach, and MICMAC analysis has been used to classify the barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Moreover, using an analytical hierarchical process (AHP) (e.g., or Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) (e.g., Jasiulewicz-Kaczmarek et al, 2021) besides the ISM-MICMAC to evaluate the importance of the identified criteria and factors have been designed by other scholars recently. Thirdly, many scholars have employed Structural Equation modelling (SEM) to validate the conceptual model emanated from the ISM-MICMAC approach (e.g., Khaba et al, 2020;Ullah & Narain, 2020).…”
Section: Quantitative Research Design: Micmac-ismmentioning
confidence: 99%
“…Moreover, using an analytical hierarchical process (AHP) (e.g., or Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) (e.g., Jasiulewicz-Kaczmarek et al, 2021) besides the ISM-MICMAC to evaluate the importance of the identified criteria and factors have been designed by other scholars recently. Thirdly, many scholars have employed Structural Equation modelling (SEM) to validate the conceptual model emanated from the ISM-MICMAC approach (e.g., Khaba et al, 2020;Ullah & Narain, 2020).…”
Section: Quantitative Research Design: Micmac-ismmentioning
confidence: 99%
“…These selected barriers were renumbered and recoded from B (barrier) to BM (barrier for model). The use of the ISM technique is appropriate because the representation and interpretation of the interactions among 15 barriers (considerably large) require a well-established modeling approach [ 90 ].…”
Section: A Real-case Application Of the Proposed Modelmentioning
confidence: 99%
“…ISM model was developed by extracting the top 15 barriers from Table 5 because the increased variables may escalate the complexity of ISM methodology [49]. These selected barriers were [90]. ISM is a holistic social system engineering technique used to model multilevel hierarchical structural cross-domain relationships based on mathematical operations.…”
Section: Causal Model Of Barriersmentioning
confidence: 99%
“…According to Ullah and Narain( 2021 ), an initial digraph, containing transitive links, was constructed using the information from the final reachability matrix and level partitioning (Fig. 1 ).…”
Section: Results and Data Analysismentioning
confidence: 99%